KOMPETENSI, KOMUNIKASI, KESELAMATAN DAN KESEHATAN KERJA TERHADAP KINERJA KARYAWAN PT ADHI GUNA PUTERA - Ifan Rospela; Ellin Herlina; Mahfud (PT. Berkah Digital Teknologi, 2022)
Purpose: To determine the effect of competence, communication on performance, occupational safety and health of employees partially at PT ADHI GUNA PUTERA Indramayu Representative Office. Research Methodology: This research uses quantitative methods. Data were collected by distributing questionnaires directly to 60 respondents. Four hypotheses were formulated in this study and tested using multiple regression analysis, classical assumption test, t test, and f test. Results: This study indicate that competence and occupational safety and health (OHS) have a significant and significant effect on employee performance, meanwhile communication has no effect and is not significant on employee performance, and simultaneously competence, communication, occupational safety and health (OHS) has a significant influence on employee performance. Sequentially the factors that affect employee performance are occupational safety and health (OHS), competence, communication. Therefore, the most influential factor in this research is occupational safety and health (OHS). Limitations: The study is limited to only one representative office of PT ADHI GUNA PUTERA Indramayu and may not be generalizable to other offices or companies., The sample size is small, which may affect the generalizability of the results, The study only uses quantitative methods and does not take into account other factors that may affect employee performance, such as motivation, work environment, and company culture. Contribution: This study can be useful for management at PT ADHI GUNA PUTERA Indramayu Representative Office to improve employee performance by focusing on competence and occupational safety and health. The study can also be useful for other companies as a reference for the impact of competence and OHS on employee performance. The study can contribute to the fields of Human Resource Management, Occupational Safety and Health, and Organizational Behavior.